PRODUCING BACTERIAL CELLULOSE FROM OIL PALM SAP AS A WOUND DRESSING MATERIAL - Joshua Nicholas Tambunan; Wardatul Husna Irham (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to utilize oil palm sap into bacterial cellulose (nata) with the assistance of Acetobacter xylinum bacteria which is then applied as a material for making wound dressings. Bacterial cellulose has a high absorption capacity and is hydrophilic so it supports optimal wound healing. This study used a non-factorial Complete Randomized Design (CRD) method consisting of three treatment stages, namely treatment P1 with a fermentation time of 8 days, treatment P2 with a fermentation time of 10 days, and treatment P3 with a fermentation time of 12 days. The results showed that fermentation time affected the thickness and absorption capacity of the produced bacterial cellulose. Treatment P3 produced bacterial cellulose with an average thickness of 15.8 mm and a better absorption capacity of 3.68 g. All the test results that have been carried out (membrane thickness, absorption capacity, tensile strength and wound dressing quality test) in the P3 treatment concluded that the cellulose produced by the Acetobacter xylium bacteria is in the form of pure cellulose which has high mechanical strength and absorption capacity so that it is suitable for use as a wound dressing material.